Dinamika Formulasi Kebijakan dalam Pengembangan Wisata Minat Khusus (Studi pada Kampung Tunagrahita Desa Karangpatihan Kabupaten Ponorogo) - Miftakhul Laily , Yaen; Setyowati, Endah; Hayat, Ainul (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
This research aims to identify and analyze the dynamics of policy formulation in the development of special interest tourism villages in the mentally retarded village of Karangpatihan Village, Ponorogo Regency, where there are problems with the mentally retarded community which causes them to be unable to fulfill their daily needs, resulting in poverty in the community. The aim of this research is to provide an alternative or policy solution for tourist villages that can be adapted to basic human needs, namely special interest tourism. The results of this research show that there is tourism potential that needs to be developed by looking at four factors that influence the formulation of alternative tourism village policies, namely the first is an idea where an idea is used to strengthen strategies and innovations to stabilize and improve the function and role of social areas by fostering mentally retarded communities, second is the government's interest To increase the income of the mentally retarded community, the third is an institution involved in developing special interest tourism villages that coordinate with each other in empowering the mentally retarded community. fourth is the individual aspect that supports the development of tourist villages. Through these four aspects, a new idea emerged regarding sharing tourism villages which was promoted with the concept of special interest tourism, namely special interest sharing tourism which had never been initiated in various regions before.